Analysis of the Difficulty of Understanding Concepts and Creative Thinking of Students in Mathematics through Problem-Based Learning in Students of SMA Angkasa Lanud Soewondo - Riadi Riadi; Bornok Sinaga; Edi Syahputra (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
This study aims to determine the level of students' mathematical concept understanding and creative thinking skills who are taught using a problem-based learning model, to find out the description of the student's answer process in learning using a problem-based learning model, to determine the difficulties in the process of understanding concepts and mathematical creative thinking of students who are taught using problem-based learning models, as well as to find out the active activities of students during the learning process using problem-based learning models. Data were obtained through tests of students' conceptual understanding and creative thinking tests, interviews with students and teachers, observations or observations by observers, and documentation. This research uses qualitative data analysis using Miles and Huberman's model, namely data reduction, display data, and conclusion drawing / verification data. The subjects of this study involved class X SMA Angkasa 1 Lanud Soewondo who were treated with the application of a problem-based learning model in the odd semester of the 2020/2021 school year, totaling 21 people with three-variable linear equation system material as many as 4 items in essay form. Based on the results of the study, there were 21 students with 'very low' creative thinking skills and 14% 'very low' creative thinking skills, 14% 'low' creative thinking skills, 43% 'medium' creative thinking abilities, 43% thinking skills creative 'high' as much as 19%, and 'very high' creative thinking ability as much as 10%.